Cancer control in the Caribbean island countries and territories: some progress but the journey continues. Issue 9 (September 2019) - Spence, Dingle; Dyer, Rachel; Andall-Brereton, Glennis; Barton, Michael; Stanway, Susannah; Argentieri, M Austin; Bray, Freddie; Cawich, Shamir; Edwards-Bennett, Sophia; Fosker, Christopher; Gabriel, Owen; Greaves, Natalie; et al.
Summary: Cancer causes a fifth of deaths in the Caribbean region and its incidence is increasing. Incidence and mortality patterns of cancer in the Caribbean reflect globally widespread epidemiological transitions, and show cancer profiles that are unique to the region. Providing comprehensive and locally responsive cancer care is particularly challenging in the Caribbean because of the geographical spread of the islands, the frequently under-resourced health-care systems, and the absence of a cohesive approach to cancer control. In many Caribbean countries and territories, cancer surveillance systems are poorly developed, advanced disease presentations are commonplace, and access to cancer screening, diagnostics, and treatment is often suboptimal, with many patients with cancer seeking treatment abroad. Capacity building across the cancer-control continuum in the region is urgently needed and can be accomplished through collaborative efforts and increased investment in health care and cancer control.